PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN WISATAWAN MELAKUKAN AKTIVITAS DIVING PADA BLUE SEASON BALI - Saraswati, Ni Putu Eka Citra; Kusuma Negara, I Made; Wikanatha Sagita, Putu Agus (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 1 (2021): Jurnal IPTA (July 2021), 2021)
In the era of Marketing 4.0, the rapid digitization has created a new face of competition reflected by shifting business practices, as well as consumer behavior from pre-purchase to post-purchase. Aside from companies that are constantly adaptive to technological advancements, consumers are becoming increasingly social and communal, so marketers need to understand new customer paths, and synergize online and offline interactions. This research aims to analyze the influence of electronic word of mouth towards tourist’s decision to do diving activities in Blue Season Bali. The technique of determining the sample used purposive sampling through distribution of questionnaires to 100 tourists who have experienced diving and accessed Blue Season Bali information on social media and website. This research applies data collection techniques which include: observation, interviews, questionnaires, literature study, and documentation. Multiple linear regression was used as an analytical technique to measure the influence of variable X on variable Y with SPSS software version 18. The research findings show that the intensity variable (X1) partially has no positive and significant effect on decision to do diving activities (Y) with sig. value 0,812>alpha 0,05. Valence of opinion variable (X2) partially has a positive and significant effect with sig. value 0,010<alpha 0,05. Content variable (X3) partially has a positive and significant effect with sig. value 0,000<alpha 0,05. Intensity, valence of opinion, and content simultaneously have a positive and significant effect with sig. value 0,000<alpha 0,05. The multiple linear regression test implies the results of regression equation, Y=13,580+(-0,046)X1+0,617X2+0,351X3+e, with coefficient of determination of 33%.